MENUMBUHKAN KREATIVITAS DENGAN MODEL PEMBELAJARAN: TINJAUAN PUSTAKA - Siti Muntamah, Bening; Fardana N, Nur Ainy (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2024)
This research aims to discuss learning models that can help teachers foster students' creativity. Creativity is one of the skills that a person needs in his life, and creativity can develop because it is not something static, so it is important to provide the right stimulus. This research uses a literature study. The literature used is in the form of publications collected from the Web of Science and Scopus databases in the period 2014–2023. The keywords used were "creativity" AND "learning model". From these keywords, 588 articles were obtained, which were then filtered, and 8 articles were selected. The results of the article review Some of the learning models obtained are as follows: cooperative learning, project-based learning (PjBL), problem-based learning (PBL), guided inquiry learning model, SSCS learning model, and science-entrepreneurship learning model. Students who are given a stimulus tend to have more abilities than students who are not given a stimulus, as well as creativity.